A Comparative Study of High-Resolution Ultrasonography with Clinical Examination in the Assessment of Peripheral Nerve Involvement in Leprosy - Kabra, Nimisha; Sinha, Rajesh; Sinha, Neetu; Gupta, Ruchi; Jaiswal, Aditya A. (Indian Journal of Radiology and Imaging, 2025)
Peripheral nerve involvement is a well-established feature of leprosy. However, it may go unnoticed by clinicians due to a decline in clinical examination skills. High-resolution ultrasonography (HRUS) offers the advantage of identifying subclinical nerve involvement at an earlier stage.This article aims to evaluate and compare the effectiveness of HRUS and clinical examination in detecting peripheral nerve involvement in leprosy, the correlation of sonological findings with clinical findings, and the calculation of sensitivity, specificity, and predictive values of HRUS taking clinical examination as the reference method.This cross-sectional observational study was conducted over 1.5 years involving 60 newly diagnosed leprosy patients. Clinical assessment and sonographic evaluation of five nerve pairs (ulnar, median, greater auricular, common peroneal, and posterior tibial) were done. Findings were recorded, analyzed, and compared.HRUS detected abnormalities in 111 of 600 (18.5%) of all nerves, surpassing the 90 of 600 (15%) nerves detected clinically. HRUS parameters demonstrated substantial agreement with clinical findings, with Cohen's kappa values of 0.740 for cross-sectional area, 0.246 for hypervascularity, and 0.166 for hypoechogenicity. The overall diagnostic performance of HRUS reported a sensitivity of 86.7%, specificity of 93.5%, and positive predictive value of 70.3% with a negative predictive value of 97.6%.This study highlights the critical role of HRUS in detecting and monitoring leprosy neuropathy, emphasizing its superiority over clinical examination in identifying both early and advanced nerve involvement.
Keywords: high-resolution ultrasonography; leprosy; ultrasonography